Association Between Duration of Active Labour and Severe Post Partum Hemorrhage - Hameed, Nibahat; Akhtar, Naheed; Qadir, Uzma; Gul, Faiza (Indus Journal of Bioscience Research, 2025)
Background: Major postpartum hemorrhage (PPH) is one of the primary causes of maternal morbidity, and by far the prevalent severe maternal complication in high income countries. Although the developments in the field of obstetrics have improved, the occurrence of PPH has been increasing. Obstetric practice changes such as induction of labor, epidural, and oxytocin augmentation have changed the patterns of labor and are thought to be contributing factors. According to the World Health Organization: prolonged active labor lasting 12 and more hours, after 4 cm dilation of the cervix. Nonetheless, the fact that the total active labor time is associated with PPH is questionable. Objective: To evaluate the association between the duration of active labor and the incidence of PPH in women with intended vaginal deliveries. Methods: Descriptive correlation research was done in the field of obstetrics and gynaecology in MTI- Khyber Teaching Hospital Peshawar, between October 2024 and April 2025. One hundred and nine women were recruited to have vaginal delivery. The amount of labor was documented and PPH was diagnosed based on the operational definitions. Correlation analysis was carried out, as well as stratified assessments. Results: Prolonged labor (>12 hours) occurred in 31.9% of participants, and PPH was observed in 18.7%. Pearson correlation analysis demonstrated a significant positive association between labor duration and PPH (r = 0.324, p = 0.002). Stratified analyses by age, residence, socioeconomic status, and previous PPH history confirmed the robustness of this association. Conclusion: Prolonged active labor is significantly associated with an increased risk of PPH. Early recognition, timely intervention, and vigilant intrapartum monitoring are essential to reduce maternal morbidity and improve obstetric outcomes. Further multicenter research is recommended to validate these findings.